Design of a hyperbaric chamber for pressure testing - Mohamad Sazali, S.F.B. (EDP Sciences, 2014)
A hyperbaric chamber is an application of a pressure vessel to test the integrity of components and equipments subjected to high pressure. The chamber comprises of several main parts such as a shell, heads, instrumentation attachments, threaded fasteners and support. This paper describes the design of hyperbaric chamber for pressure testing that compiles to the ASME Boiler and Pressure Vessel code. The design approach adopted is the "design by formula" method. A structural analysis of the hyperbaric chamber with a cylindrical shell and a vertical orientation, based on an operating pressure of 34.5 MPa, was done. The analysis of the stress distribution shows that the normalized principal stresses acting on the chamber are within the yield envelop based on the maximum distortional energy criteria. Â© 2014 Owned by the authors, published by EDP Sciences.